In-vitro Cytotoxic and Anti-vibro Cholerae Activities of Methanol Roots Extracts of Morinda citrifolia L (Noni) - Umaru, Isaac John; Konka, Daniel; Kingsly, Iseko Iyoko; Asare, Solomon Ossom; Hassan, Okrah George; Oteng, Joseph; Akafa, Tensaba Andes; Umaru, Kerenhappuch Isaac (Darul Yasin Al Sys, 2025)
Knowledge on medicinal properties of plants has extensively been applied all over the World to cure or ameliorate suffering of mankind. The use of remedies from plant origin covers a wide variety of maladies and constitutes an alternative way to antibiotics, which is otherwise no longer promising due to the generalized antibiotic resistance among pathogenic microorganisms. The majority of epidemic Vibrio cholerae strains have become resistant to multiple antimicrobial agents for many reasons, including mutations, horizontal gene transfers, etc. Therefore, secondary means of treatment are needed to overcome this impediment in combating cholera. Morinda citrifolia roots extensively used in traditional medicine. Therefore, the present study aims to evaluate the In-vitro Cytotoxic and Anti-vibro Cholerae Activities of Methanol Roots Extracts of Morinda citrifolia against V. cholerae isolates. Methods: Initially, different concentration of the extracts materials was subjected to qualitative phytochemical screening. Anti-V.cholerae activities were assessed by performing MIC (minimum inhibitory concentration) test using disc diffusion method with different concentrations (1.25, 2.25, 5.00, 8.00, 10.00mg/ml) where standard discs of gentamycin and meropenem (10 μg/disc) were used. Further, Brine shrimp lethality bioassay was done to evaluate the extracts’ cytotoxic activities using different concentrations (5,10, 20, 50, 100, 200, 400, 800μg/ml) against vincristine sulphate. Results: The preliminary screening confirms the presence of convenient phytochemical constituents like flavonoids, alkaloids, glycosides, tannins, etc., and are liable for the emergence of the antibacterial activities in different strains. The minimum inhibitory concentrations of methanolic Morinda citrifolia roots was found to be (a) 1.25, (b) 2.25, (c) 5, (d) 8, and (f) 10 mg/ml, respectively. Moreover, 100% mortality was observed only at the highest concentration (800 μg/ml). In comparison, the rest of the test concentration showed less than 90% mortality at the highest concentration (400 μg/ml). Conclusions: The Morinda citrifolia roots possess significant phytochemicals and showed potential anti-V. cholerae activities with mild toxicity. Hence, Morinda citrifolia (L.) roots may be recommended as potential phytotherapy against cholera disease.